Effects of hydrogen enrichment on combustion characteristics of a CI engine. (13th April 2017) - Yilmaz, I.T.; Demir, A.; Gumus, M.
Abstract: In this study a comprehensive investigation of combustion (cylinder pressure, rate of pressure rise, ignition delay) and heat release (rate of heat release, cumulative heat release and center of heat release) parameters of a four cylinder, turbocharged, common rail compression ignition engine running with hydrogen addition was carried out. Hydrogen was send into intake manifold by using a mixing chamber. Flow rates of hydrogen were 20 lpm and 40 lpm for achieving constant speed of 1750 rpm at 50 Nm, 75 Nm and 100 Nm engine loads (EL). Results showed that maximum cylinder pressures (CPs), rate of pressure rises (ROPRs) and ignition delays (IDs) raised, rate of heat releases (ROHRs) decreased and combustion durations (CDs) extended with hydrogen addition. Highlights: Effects of hydrogen on combustion characteristics of a CI engine were investigated. Hydrogen was used as secondary fuel while diesel was used as main fuel. Cylinder pressures, rate of pressure rises and ignition delays increased. ROHRs raised at the pilot injection stage but decreased at the main injection stage. Combustion durations extended with hydrogen addition at low and medium loads.